2008
DOI: 10.1249/mss.0b013e318160740f
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Acute Traumatic Primary Patellar Dislocation

Abstract: Primary patellar dislocation is not a negligible cause of morbidity among young male adults. It can be concluded that hemarthrosis and MPFL rupture are the definite signs of an acute traumatic primary patellar dislocation. Height and weight were significant risk factors, whereas poor physical performance was not associated with primary patellar dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
217
4
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(240 citation statements)
references
References 32 publications
6
217
4
13
Order By: Relevance
“…First, it has been previously shown that some hereditary traits, developmental factors and personal characteristics such as family history of patellar dislocation, structural abnormalities, female sex and a body mass index of greater than 25 are associated with increased risk of patellar instability [20][21][22]. Hence, one could conclude that both symptomatic and asymptomatic knees of patients with unilateral patellar instability were predisposed to dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been previously shown that some hereditary traits, developmental factors and personal characteristics such as family history of patellar dislocation, structural abnormalities, female sex and a body mass index of greater than 25 are associated with increased risk of patellar instability [20][21][22]. Hence, one could conclude that both symptomatic and asymptomatic knees of patients with unilateral patellar instability were predisposed to dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of patellar dislocation is between 7 [2] to 77 per 100,000 people per year [3], with a marginally greater incidence in females [2,4]. The term first-time patellar dislocation (FTPD) represents the first episode that the patella disengages completely from the femoral trochlear.…”
Section: Introductionmentioning
confidence: 99%
“…They can be seen with some predisposing conditions such as trochlear dysplasia, patella alta, and extremity alignment disorder, or they can be encountered in normal patellofemoral joint after serious traumas (2).…”
Section: Introductionmentioning
confidence: 99%